2016
DOI: 10.9741/23736658.1034
|View full text |Cite
|
Sign up to set email alerts
|

Depression and anxiety one month after stroke

Abstract: Depression and anxiety after stroke negatively affect patient outcomes; however, health care professionals may overlook poststroke depression and anxiety while they focus on the physical disabilities of patients soon after a stroke. The purpose of this study was to investigate the prevalence and predictors of depression, anxiety, or both concurrently at one month after stroke. We conducted a cross-sectional, descriptive study in a sample of 231 hospitalized patients with ischemic stroke in Korea. Data were col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
(71 reference statements)
0
1
0
Order By: Relevance
“…6,7 The prevalence of post-stroke anxiety is 6-8 times higher than the prevalence of anxiety in the general population. 8 Interviews with 5 post-stroke patients who were undergoing outpatient care in Semarang City found that the patient said that every day he felt anxious about the bad things that could happen, such as repeated strokes, more severe symptoms, and changes in the situation. Qualitative research shows that psychological pressure causes post-stroke patients to experience self-loss (patients say they like it when they come back), feel frightened (patients say the stroke occurred without prior warning) and feelings of isolation (patients say their life is very lonely).…”
Section: Introductionmentioning
confidence: 99%
“…6,7 The prevalence of post-stroke anxiety is 6-8 times higher than the prevalence of anxiety in the general population. 8 Interviews with 5 post-stroke patients who were undergoing outpatient care in Semarang City found that the patient said that every day he felt anxious about the bad things that could happen, such as repeated strokes, more severe symptoms, and changes in the situation. Qualitative research shows that psychological pressure causes post-stroke patients to experience self-loss (patients say they like it when they come back), feel frightened (patients say the stroke occurred without prior warning) and feelings of isolation (patients say their life is very lonely).…”
Section: Introductionmentioning
confidence: 99%